2017
DOI: 10.1093/mnrasl/slx199
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pair cascades on the high-energy spectral cut-off in gamma-ray bursts

Abstract: The highly luminous and variable prompt emission in Gamma-Ray Bursts (GRBs) arises in an ultra-relativistic outflow. The exact underlying radiative mechanism shaping its non-thermal spectrum is still uncertain, making it hard to determine the outflow's bulk Lorentz factor Γ. GRBs with spectral cutoff due to pair production (γγ → e + e − ) at energies E c 10 MeV are extremely useful for inferring Γ. We find that when the emission region has a high enough compactness, then as it becomes optically thick to scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…In case the structure of the jet can be modeled as having sharp edges, then θ c = θ j , where θ j is the half-opening angle of the jet. In these GRBs, compactness arguments (e.g., Lithwick & Sari 2001;Gill & Granot 2018b) dictate that Γ > 100, otherwise opacity due to γγ-annihilation (i.e., γγ → e − + e + ) would prevent the radiation of gamma- ray photons. Modeling of the radio/optical/X-rays afterglow emission from GRB 170817A, both using semi-analytical models (e.g., Gill & Granot 2018a;Lamb & Kobayashi 2018;Troja et al 2018), as well as numerical simulations (e.g., Granot et al 2018;Lazzati et al 2018;Margutti et al 2018;Kathirgamaraju et al 2019) of structured jets, has revealed that the line-of-sight is significantly off-axis, with 20 • θ obs 28 • and θ c ∼ 5 • .…”
Section: Collapse Time From Em Delaymentioning
confidence: 99%
“…In case the structure of the jet can be modeled as having sharp edges, then θ c = θ j , where θ j is the half-opening angle of the jet. In these GRBs, compactness arguments (e.g., Lithwick & Sari 2001;Gill & Granot 2018b) dictate that Γ > 100, otherwise opacity due to γγ-annihilation (i.e., γγ → e − + e + ) would prevent the radiation of gamma- ray photons. Modeling of the radio/optical/X-rays afterglow emission from GRB 170817A, both using semi-analytical models (e.g., Gill & Granot 2018a;Lamb & Kobayashi 2018;Troja et al 2018), as well as numerical simulations (e.g., Granot et al 2018;Lazzati et al 2018;Margutti et al 2018;Kathirgamaraju et al 2019) of structured jets, has revealed that the line-of-sight is significantly off-axis, with 20 • θ obs 28 • and θ c ∼ 5 • .…”
Section: Collapse Time From Em Delaymentioning
confidence: 99%
“…However, the recent short GRB170817A associated with the NS-NS merger gravitational wave event GW170817 provides stricter and more robust constraints on the value of b. Detailed theoretical modeling (Gill & Granot 2018) together with the very elaborate afterglow observations from this event, and in particular the detection of super-luminal motion of the radio flux centroid with an apparent velocity of β app = 4.1 ± 0.5 (Mooley et al 2018), clearly imply that the late time afterglow emission arises primarily from near the energetic narrow core of a relativistic jet viewed from well outside of its core. The jet structure and viewing angle implied by these observations result in clear predictions for the afterglow linear polarization (Gill & Granot 2018).…”
Section: Likely Origin and Configuration Of The Magnetic Fieldmentioning
confidence: 99%
“…However, it is only true in the case when the effect of pair production is ignored. In a fully time-dependant model this could be 1.5 -2 times lower (Gill & Granot 2018).…”
Section: Joint Gbm-lat Analysismentioning
confidence: 96%